Synthesis of La0.8Sr0.2Co0.9Fe0.1O3-δ perovskite oxide catalyst and the geometric modification of a catalytic converter for hydrocarbon and carbon monoxide emission reduction - Patel, Kuldip; Subhedar, Dattatraya; Patel, Femina; Patel, Gaurav (Frontiers in Chemical Engineering, 2026)
Increasing environmental concerns caused by vehicular emissions have intensified the search for the design and development of non-noble metal catalysts for catalytic converter devices as potential replacements for conventional Pt-, Pd-, and Rh-based noble metal catalysts. This research highlights the development and evaluation of an alternative to conventional catalysts through the synthesis of non-noble metal perovskite-based catalysts and the design modification of a catalytic converter. A non-noble metal catalyst, La0.8Sr0.2Co0.8Fe0.2O3 (LSCF), was synthesized by co-precipitation, coated onto a ceramic monolith of a catalytic converter, and examined for effectiveness under petrol fuel laboratory test setup. The synthesized catalyst was also analyzed using SEM, XRD, and EDX to study surface morphology and confirm the crystal structure. The catalytic converter housing assembly was modified by integrating design modifications and analyzed through computational simulations to investigate velocity profile, pressure distribution, and reaction behavior. Among the three catalytic converter design configurations with diffuser cone angles of 8°, 10°, and 14°, the first was selected as it showed a favorable gas flow pattern, pressure distribution, and velocity profile. The entire module was then experimentally evaluated on a petrol fuel laboratory test setup to assess emission performance under varying loads and speeds. Experimental emission tests revealed a significant reduction in hydrocarbon (HC) and carbon monoxide (CO) emissions compared to engines without a catalytic converter. The results demonstrate that the synthesized La0.8Sr0.2Co0.9Fe0.1O3-δ non-noble metal catalyst, combined with the modified catalytic converter design, effectively reduces vehicular emissions and provides an alternative and practical approach to noble metal catalysts. A noticeable reduction in CO and HC exhaust emissions was achieved using the LSCF catalyst for an automotive catalytic converter.